ETHICAL AND CLINICAL CONSIDERATIONS IN THE USE OF RESTRAINTS FOR PATIENT SAFETY IN INTENSIVE CARE UNITS - Aina Fitri; Rosa Galica Gita Gressia; Isni Hijriana; Gadis Halizasia (Universitas Bina Bangsa Getsempena, 2025)
The use of physical restraints on patients in intensive care units (ICUs) is a common intervention aimed at ensuring patient safety, particularly in preventing the dislodgement of vital invasive devices. However, this practice raises ethical and clinical dilemmas due to the complex considerations involved. The aim of this study was to explore the ethical and clinical considerations in the use of restraints for patient safety in the intensive care setting. This research employed a qualitative phenomenological design, with data collected through in-depth interviews involving eight participants in the intensive care unit. Data were analyzed using the Colaizzi method. The study identified three major themes: considering the patient's needs, preventing the dislodgement of invasive devices, and experiencing contradictory feelings. The findings highlight the need for clearer, standardized policies on the use of restraints in intensive care units that incorporate both ethical and clinical perspectives.